2019
DOI: 10.3390/s19051104
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Convolutional Neural Network Inspired by Auditory Perception for Underwater Acoustic Target Recognition

Abstract: Underwater acoustic target recognition (UATR) using ship-radiated noise faces big challenges due to the complex marine environment. In this paper, inspired by neural mechanisms of auditory perception, a new end-to-end deep neural network named auditory perception inspired Deep Convolutional Neural Network (ADCNN) is proposed for UATR. In the ADCNN model, inspired by the frequency component perception neural mechanism, a bank of multi-scale deep convolution filters are designed to decompose raw time domain sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…In Figure 9 , the used network is compared with DNN [ 13 ], ADCNN [ 15 ], DepthCNN [ 16 ], CDBN [ 17 ], and CRNN [ 18 ]. HRNet is the hybrid routing network method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 9 , the used network is compared with DNN [ 13 ], ADCNN [ 15 ], DepthCNN [ 16 ], CDBN [ 17 ], and CRNN [ 18 ]. HRNet is the hybrid routing network method.…”
Section: Methodsmentioning
confidence: 99%
“…An end-to-end learning network, called the auditory perception inspired deep CNN (ADCNN), is an efficient network architecture in signal feature extraction, and the method transform signals from the temporal domain to the frequency domain. The deep representation of raw signal can be separated; this method achieves satisfactory performances in underwater acoustic target classification [ 15 ]. The original signal data are input into the depthwise separable CNN (DSCNN) in the temporal domain.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other methods, it is shown that the proposed method is capable of providing sufficient processing gain and effectively enhancing the narrowband discrete components in a ship-radiated acoustic signal. This is also of great significance for target recognition [21,22] and classification [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, as the most popular deep learning model, the deep neural network (DNN) has attracted the interest of scholars in the field of UATR [16]. Yang et al combined the auditory perception principle and convolutional neural network (CNN) to propose an auditory perception-inspired deep convolutional neural network (ADCNN), which used a CNN to extract features of different frequency components from signals and merged them at the fusion layer to achieve the classification of acoustic targets [17]. Choi et al used the absolute values of matrix elements in the cross-spectrum density matrix (CSDM) to generate two additional matrices as input data and used them for training the CNN model [18].…”
Section: Introductionmentioning
confidence: 99%